A comparative study of maternal-neonate abdominal and kangaroo (skin-to-skin) skin contact immediately after birth on maternal attachment behaviors up to 2 months - Mohadse Adeli; Maryam Aradmehr (Wolters Kluwer Medknow Publications, 2018)
Background: Early skin-to-skin maternal-neonate contact during the 1st h following birth prepares both mother and baby to establish a two-way, interactive pattern of interaction. There are few studies on the use of kangaroo care method in term infants and maternal postpartum behavior. Objective: The present study aimed to compare abdominal and kangaroo skin contact on maternal attachment behaviors. Settings and Design: This single-blind randomized clinical trial was performed on 68 eligible pregnant women in Torbat Heydariyeh in 2015. Materials and Methods: Individuals were randomly divided into experimental groups (kangaroo skin contact) and control group (abdominal skin contact). Maternal attachment behaviors were observed for 15 min during 1 h postpartum. Each minute was divided into two 30 s, during the first and second 30 s of which the maternal behavior was observed and recorded using a checklist of behavior. Attachment behaviors were assessed using an attachment behavior checklist (including three types of emotional, proximity-seeking, and caring behaviors). Statistical Analysis Used: After data coding, the analysis was performed using Kruskal-Wallis test, Chi-square test, t-test, and Mann-Whitney test in SPSS ver. 14. P < 0.05 was considered the significant level. Results: Among emotional, proximity-seeking, and caring behaviors 1 h and 2 months' postpartum in the two groups, only proximity-seeking behaviors were significantly different 2 months' postpartum (P = 0.033). The attachment behavior of 1 h (0.134) and 2 months' postpartum (0.051) did not differ significantly between the two groups. Conclusions: Kangaroo skin contact has an effect, similar to the abdominal skin contact, on the maternal attachment behaviors and has a positive effect on proximity-seeking behaviors and some components of emotional behaviors compared to abdominal skin contact.